A Circular Economy approach in the Agri-food chain: using by-products and underexploited raw materials as flours for gluten-free bakery and as coagulants for wastewater treatment - Martins, Maria Rita Beltrão Franco (2022)
Nowadays, food scarcity has been leading the agri-food stakeholders to find solutions in order to face this problem. Circular Economy has been identified as one of the successful strategies to overcome resources scarcity, besides presenting environmental advantages. Thus, applying Circular Economy fundamentals in order to use by-products and underexploited raw materials, can be considered an important contribution to overcome this problem in the future. Moreover, these ingredients fulfill the current food trends from different perspectives and are also recognized for their potential health benefits. Therefore, it is essential to study its application in food products, in order to understand its nutritional and organoleptic performance. The objectives of the present work are: to study the feasibility of a Circular Economy approach in the Agri-food chain, adding value to by-products and underexploited raw materials as flours, to produce gluten-free (GF) bread, improving its characteristics, and also to assess the use of by-products as plant-based coagulants for wastewater treatment. The studied ingredients were acorn flour as an underexploited resource, and apple flour as a by-product, being both naturally GF. Acorn flour characterization results revealed a multipurpose ingredient potential. The nutritional composition presented about 4.3% protein, 11.4% of fat content, particularly monounsaturated and polyunsaturated (oleic and linoleic acids), 11.4% of fiber, mainly insoluble, and also high minerals content (1.6%), in particular, potassium (0.70%). Bioactive compounds and antioxidant capacity have shown high values, with the following phenolic compounds identified by HPLC: rutin, catechin, ellagic acid, gallic acid, and syringic acid. Acorn flour revealed a starch content of about 50%, with spherical shaped granules, and pasting behaviour has presented a high gelatinization temperature (85ºC), with low breakdown, and higher retrogradation consistency. Acorn flour rheological performance has shown a positive impact in the firmness, cohesiveness, and viscoelastic characteristics of the dough, influencing mixing and pasting curves, as well. These effects were revealed with an acorn flour incorporation level of 23% in dough’s formulation. Consequently, GF bread also presented improved technological characteristics. Additionally, nutritional, functional, and sensorial profile have improved with acorn flour incorporation. In particular, acorn flour allowed to develop breads with higher content of fiber, unsaturated fatty acids (oleic and linoleic), minerals, bioactive compounds, and higher antioxidant capacity. Moreover, rutin, catechin, and ellagic acid, were present in the breads with acorn flour incorporation, while gallic acid and syringic acid increased their concentration in comparison with control bread. Combining acorn flour with sourdough, joined both positive features, leading to GF bread with technological, nutritional and functional improved characteristics. Besides the expected acidification from sourdough, acorn flour decreased the rate and extent of starch hydrolysis, increased unsaturated fatty acids, and polyphenols content. Concerning apple flour, its nutritional and functional characterization revealed approximately 1.3% protein, 0.5% of fat content, 12.9% of fiber, mainly insoluble, and 5.5% of ash content, high bioactive compounds and antioxidant capacity. Apple flour was added to GF bread as a sustainable sweetener, acting as a natural sugar source, and leading to a low-intermediate glycemic index GF bread. The results revealed an improvement in technological, and sensorial characteristics of the bread, with an increase of bioactive compounds content and antioxidant capacity. Fulfilling the second objective of the present work, and closing the production cycle, plantbased coagulants from by-products (chestnut burr, acorn peel, olive leaf, and grape stem) were tested in the coagulation-flocculation-decantation of elderberry wastewater treatment process, before applying photo-Fenton methodology. The plant-based coagulants achieved higher efficiency at pH 3.0. The pre-treatment using the CFD process is important to reduce turbidity and total suspended solids in order to improve the efficiency of the photo-Fenton process, due to better penetration of the radiation. The use of plant-based coagulants from by-products, is a promising strategy for wastewater treatment, while at the same time, enabling re-using and adding value to agri-food industry resources, that were being wasted, and reaching environment-friendly solutions as well.